Hubungan antara Kedisiplinan Belajar Siswa dengan Hasil Belajar - Trio Efendi, Moh.Bagus; Kinanthy Karamoy, Yurike; Nur Budiono, Arifin (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
Discipline is the main key to success in success. Disciplined students will certainly achieve success in learning. However, the facts that occurred in the field or more precisely at Diponegoro Wuluhan Junior High School, showed that there were 7 students who were not disciplined in learning. The purpose of this study is to determine the relationship between discipline and student learning outcomes. This study used a correlational type quantitative approach. With respondents 120 grade VII students out of 65 students taken overall using saturated samples. The data collection method used in this study is the questionnaire method. Analyze the data using the coefficient formula by finding r Product Moment. The results showed that the calculated r value was 0.979 and the rtable value was 0.979 with the number N 65, which showed that the two variables correlated with a strong degree of relationship with the correlation form y. Thus the conclusion was obtained: There is a relationship between student learning discipline and student learning outcomes at SMP Diponegoro Wuluhan Keywords: Disciplines Learning; Result Learning